Mindfulness in Organizations: Foundations, Research, and Applications - Reb, Jochen Matthias (Institutional Knowledge at Singapore Management University, 2015)
Mindfulness techniques, having long played an important role in contemplative traditions around the world, are now recognized as having the potential to transform workplaces. As interest in the role of mindfulness in organizational settings continues to increase, this timely book fills a gap in the literature by providing an overview of the latest theoretical and empirical research on workplace mindfulness. It brings together world-leading scholars to explore the foundations, key discussions, diversity of approaches and applications of mindfulness in organizations. It acts as a catalyst for future research on the topic by suggesting research directions and stimulating organizational researchers to embark on new projects involving mindfulness. Furthermore, it provides valuable ideas for implementing mindfulness programs in organizations, for teaching mindfulness in business contexts, and for coaching with mindfulness. This must-read book will appeal to researchers and professionals in the fields of organizational behavior, organizational psychology and employee well-being.